Loss of the SHOX gene associated with Leri-Weill dyschondrosteosis in a 45,X male - Stuppia, L (BMJ Group, 1999)
A male patient is reported with a 45,X karyotype and Leri-Weill dyschondrosteosis (LWD). FISH analysis with SHOX and SRY gene probes was carried out. One copy of both SHOX and SRY was detected in interphase nuclei, clarifying the origin of LWD and the male phenotype. Molecular results suggested that the 45,X karyotype arose through two independent events. The first occurred at paternal meiosis leading to an unequal crossing over between the short arms of the X and Y chromosomes. As a consequence, the SRY gene was translocated onto Xp, thereby explaining the male phenotype of the patient. The second event probably occurred at maternal meiosis or at the early stages of the zygote resulting in the loss of the maternal X chromosome.   Keywords: 45,X karyotype; Leri-Weill syndrome; SHOX gene